Xylopia parviflora (A. rich.) benth. Mitigates anxiety behavior and chronic mild stress-induced depression-like behavior in mice: The involvement of biogenic amine neurotransmitters, cyclooxygenase-2 and stress biomarkers in its antidepressant activity - Abdullahi A. Murtala; Elijah O. Oyinloye; Farouk A. Oladoja; Samuel M. Fageyinbo; Holiness A. Olasore; Luqman O. Ogunjimi; Akinyinka A. Alabi; Wasiu E. Olooto; Oluwatosin O. Soyinka; Abayomi S. Faponle; Oluwatoyin O. Shonde; Luqmon E. Osipitan; et al. (Pharmacological Research - Modern Chinese Medicine)
Background: Xylopia parviflora is a novel botanical in Modern Chinese Medicine that contains bioactive constituents including alkaloids, flavonoids, and terpenoids, which are the pharmacologically active components in various Chinese herbal formulations such as Coptis chinensis (alkaloid-rich herbs), Ginkgo biloba (flavonoid-rich herbs) and Artemisia annua (terpenoid-rich herbs). Objective: This investigation sought to evaluate the anxiolytic and antidepressant-like effects of the hydroethanol leaf extract of Xylopia parviflora using mouse models. We elucidated the roles of noradrenaline, serotonin, cyclooxygenase-2, and reactive oxidative species in mediating its antidepressant effects, providing a fresh perspective on the pharmacological activity of Xylopia parviflora. Methods: The acute toxicity of XPE was assessed following OECD guideline 420. Established behavioral tests were used to evaluate the anxiolytic (including the hole-board, open field, elevated plus maze, and light/dark exploration assessments) and antidepressant (encompassing the forced swim and tail suspension tests) effects of the extract. Mice received treatments of distilled water (10 mL/kg, serving as the negative control), fluoxetine (20 mg/kg, acting as the reference medication), and XPE (at doses of 50, 100, and 200 mg/kg). The concentrations of noradrenaline, serotonin, and COX-2 within the brain tissue were quantified using ELISA kits. The levels of antioxidant biomarkers were evaluated using standardized commercial assay kits. Results: The oral/intraperitoneal LD50 for the extract was established at 2000 mg/kg. In the behavioral assessments designed to measure anxiolytic effects, XPE significantly mitigated anxiety levels in mice, as evidenced by an increase in exploratory behaviors (including head dips, sectional crossings, general square crossings, rearing, and assisted rearing) and an increased time spent in the brightly illuminated compartments. Concerning the antidepressant evaluations, XPE significantly reduced depression-like behaviors in mice, which was indicated by an increased latency to immobility and a decrease in the duration of immobility. XPE was found to modulate noradrenaline and serotonin transmissions, attenuate oxidative species, and inhibit COX-2 activity. Conclusion: The findings above demonstrate that Xylopia parviflora possesses anxiolytic and antidepressant-like activities. The antidepressant property of XPE, as revealed in this study, may be attributable to the enhancement of biogenic amines (specifically noradrenaline and serotonin), the suppression of oxidative species, and the inhibition of COX-2 activity.